ANALISIS PROSES PLANNING, EXECUTION DAN REVISION DALAM PEMECAHAN MASALAH MATEMATIS DITINJAU DARI KEMAMPUAN KOGNITIF SISWA - DESY EKA PUSPITO RINI, - (2021)
This study aims to formulate a theory related to the planning, execution, and revision processes in solving mathematical problems in terms of students' cognitive abilities. This study used a qualitative approach with a grounded theory design. The research subjects were 28 students of junior high school class IX in Subang who had studied the rectangular area material. From the research results, it was concluded that there were some aspects of the planning process in solving mathematical problems such as: (1) KKT and KKS students were able to collect the available information, were able to determine the focus of problems, comprehended the problems by providing evidence or reasons, and were able to determine strategies to solve the problems. (2) KKR students tended to understand the problems even though they did not try to collect available information before as a first step to find solutions, they were capable to include evidence or reasons, and determine the strategies used to solve the problems. In the execution process in solving mathematical problems it was concluded that (1) KKT students were able to solve problems according to plan, they were also able to explain or interpret results according to plan. (2) KKS and KKR students only afforded to do well in solving the problems according to plan step, and they disposed to find it difficult when they had to explain or interpret the results according to plan. In the revision process in solving the mathematical problems of KKT, KKS and KKR students indicated that they were only able to justify the correctness of the answers and still have difficulties in checking the correctness of the answers.